2009
DOI: 10.1016/s1472-6483(10)60085-5
|View full text |Cite
|
Sign up to set email alerts
|

Single intramural leiomyoma with normal hysteroscopic findings does not affect ICSI–embryo transfer outcome

Abstract: Where there is no distortion of the endo-myometrial junction, the effect of an intramural leiomyoma on reproductive performance is controversial. The current study compared the performance of patients having a single leiomyoma and intact endometrium confirmed by hysteroscopy (study group) with that of controls having intact endometrium alone in intracytoplasmic sperm injection (ICSI) cycles. A total of 61 consecutive infertile patients were retrospectively enrolled into the study group from a computerized IVF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“…Six systematic reviews/meta-analyses have been published since 2001. 16,[20][21][22][23][24][25] These reviews greatly assist in collating the available information and help in drawing clinically meaningful conclusions from the heterogeneous data set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six systematic reviews/meta-analyses have been published since 2001. 16,[20][21][22][23][24][25] These reviews greatly assist in collating the available information and help in drawing clinically meaningful conclusions from the heterogeneous data set.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Bozdag and colleagues examined the reproductive performance of women having a single intramural leiomyoma and an intact endometrium (confirmed by hysteroscopy) versus controls, with all patients undergoing in vitro fertilization with intracytoplasmic sperm injection. 25 All had severe male factor infertility. Implantation rates and clinical pregnancy rates were virtually identical for the two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Bozdag et al demonstrated an improvement in spontaneous conception rates after the surgical removal of submucosal fibroids, but pregnancy rates following the removal of intramural or subserosal fibroids were no more improved than in the expectant management group of women with intramural or subserosal fibroids in situ [60]. A recent meta-analysis also demonstrated similar findings, with an improvement in pregnancy rates in infertile patients undergoing surgical removal of submucosal fibroids, but not in those undergoing surgical removal of intramural fibroids [27].…”
Section: Management Of Subfertilitymentioning
confidence: 95%
“…One, published subsequent to the meta-analysis just cited, is limited to women with intramural myomas. 25 Two early studies chose to investigate women seen in the first trimester for ultrasonographic examination; design shortcomings include inconsistency in time of pregnancy diagnosis and an inherent bias in which patients were referred for ultrasound examination. 51,52 Nevertheless, inclusion of these three studies does not change the overall conclusion: Uterine fibroids increase the rate of SAB.…”
Section: Fibroids and Spontaneous Abortionmentioning
confidence: 99%